2017
DOI: 10.1080/0284186x.2017.1351622
|View full text |Cite
|
Sign up to set email alerts
|

The potential of hyperpolarized 13C magnetic resonance spectroscopy to monitor the effect of combretastatin based vascular disrupting agents

Abstract: DCE-MRI and FDG-PET revealed loss of vessel functionality, impaired glucose delivery and reduced metabolic activity prior to cell death. [1-C]lactate-to-[C]bicarbonate ratios increased significantly during treatment, indicating a decline in respiratory activity driven by the onset of hypoxia. HPMRS is promising for early detection of metabolic stress inflicted by VDAs, which cannot easily be inferred based on blood flow measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Our previous studies in the C3H mammary carcinoma confirm CA4P can significantly reduce tumor perfusion for extensive periods [37][38][39], and this leads to an induction of necrosis and corresponding tumor growth inhibition [37,40,41]. Although OXi4503 is an analogue of CA4P, it is superior to the parent compound [40] because it induces greater vascular damage [42] and undergoes oxidative activation to a quinine intermediate, thereby, also giving it direct cell killing properties [43]. Indeed, our own studies using this C3H mammary carcinoma clearly show OXi4503 to have a greater effect than CA4P on the induction of tumor necrosis and subsequent inhibition of tumor growth [40].…”
Section: Discussionmentioning
confidence: 91%
“…Our previous studies in the C3H mammary carcinoma confirm CA4P can significantly reduce tumor perfusion for extensive periods [37][38][39], and this leads to an induction of necrosis and corresponding tumor growth inhibition [37,40,41]. Although OXi4503 is an analogue of CA4P, it is superior to the parent compound [40] because it induces greater vascular damage [42] and undergoes oxidative activation to a quinine intermediate, thereby, also giving it direct cell killing properties [43]. Indeed, our own studies using this C3H mammary carcinoma clearly show OXi4503 to have a greater effect than CA4P on the induction of tumor necrosis and subsequent inhibition of tumor growth [40].…”
Section: Discussionmentioning
confidence: 91%
“…Thus, in the case of therapeutic drugs working through this anti‐angiogenic pathway, Lac/Pyr or k PL would not be an adequate biomarker of therapeutic success and other strategies may be required to asses it. In this respect, both Park et al and Iversen et al point to a different ratio, hyperpolarized Lac/bicarbonate, as a better sensor of response to antiangiogenic agents (Supplementary Figure 4).
Take home messages .
…”
Section: Mrs(i)‐detectable Metabolic Hallmarks Of Cancer: Applicationmentioning
confidence: 94%
“…Four recent reports have investigated the Lac/Pyr ratio (or k PL ). Ravoori et al and Tee et al found that this ratio increases, whereas Park et al and Iversen et al found it to remain stable, when a variety of preclinical tumours (glioma, mammary carcinoma, ovarian, lung carcinoma) respond to therapy. In References 33, 35 and 36, the therapeutic agent used displayed anti‐angiogenic or vascular disrupting activity, while in Reference the drug used was an activator of PKM2.…”
Section: Mrs(i)‐detectable Metabolic Hallmarks Of Cancer: Applicationmentioning
confidence: 99%
See 2 more Smart Citations